Improved vacuum-evaporated blue perovskite light-emitting diodes with phenethylammonium chloride and guanidinium bromide synergistic post-processing modification - Liang Sun; Xiping He; Zhiyuan He; Feihu Zhang; Chencheng Peng; Ben Chen; Runda Guo; Lei Wang (Frontiers of Optoelectronics)
Abstract Metal halide perovskites have become one of the most competitive new-generation optoelectronic materials due to their excellent optoelectronic properties. Vacuum evaporation can produce high-purity and large-area films, leading to the wide application of this method in the semiconductor industry and optoelectronics field. However, the electroluminescent performance of vacuum-evaporated perovskite light-emitting diodes (PeLEDs) still lags behind those counterparts fabricated by solution methods. Herein, based on vacuum evaporation, 3D perovskite films are obtained by three-source co-evaporation. Considering the unique quantum well structure of quasi-2D perovskite can significantly enhance the exciton binding energy and improve the radiative recombination rate, leading to a high photoluminescence quantum yield (PLQY). Subsequently, the highly stable and low-defect-density quasi-2D perovskite is introduced into 3D perovskite films through post-treatment with phenethylammonium chloride (PEACl). To minimize the degradation of film quality caused by PEACl treatment, a layer of guanidinium bromide (GABr) is vacuum evaporated on top of PEACl treatment to further improve the quality of emitting layer. Finally, under the synergistic post-processing modification of PEACl and GABr, blue PeLEDs with a maximum external quantum efficiency (EQE) of 6.09% and a maximum brightness of 1325 cd/m2 are successfully obtained. This work deepens the understanding of 2D/3D heterojunctions and provides a new approach to construct PeLEDs with high performance. Graphical abstract